On one optimal way of control over thermal treatment process - N. P. Voronova; N. I. Berezovsky; E. K. Kostjukevich (Литьë и металлургия)
The aniele provides numerical solution of the problem of optimal control over two-stage processes of metallurgical production. As an optimization criterion the author takes duration of the process with preset approximation accuracy to the distribution demand when process duration is fixed.